ROMANIAN RURAL LODGINGS: HOW MANY SURVIVED OVER A DECADE? A PRELIMINARY STUDY FOCUSED ON THE RURAL LOCALITIES HOSTING 10 OR MORE ACCOMMODATION UNITS - Cornelia POP; Cristina BALINT (Studia Universitatis Babeş-Bolyai Negotia, 2017)
To the best of our knowledge, no previous study exits on the survival of tourist accommodation units and/or on the economic entities related to these accommodations in Romania. Therefore no such study exists in relation with the rural accommodation units. Through the present study we try to make a small step in filling the research gap regarding the survival of extant rural accommodation units in a developing country, Romania. The findings show an overall simple survival rate (SSR) of 38.21%. The existence of tourist attractions (spa/mountain resorts and World Heritage Sites) improve the extant lodgings SSR, while exceptions exist in the counties of Sibiu, Neamt, Suceava, Cluj and Harghita. The dominant surviving accommodation units are the rural pensions. The owners/operators of the survivor lodgings are mainly individual enterprises, though between 2005 and 2016 the number of operators registered as LLCs increased. Indirectly, the findings also imply that most of the survivor lodgings can be considered lifestyle enterprises.